Factors Associated With State Mandate of Nursing Home Staff Testing During COVID-19. (17th December 2021) - Simpson, Elizabeth; Miller, Edward; Wylie, Molly; Beauregard, Lisa; Nadash, Pamela; Gusmano, Michael
Abstract: COVID-19 has presented challenges for nursing homes (NHs) and other congregate living settings which serve older adults at high risk for morbidity and death from the virus. This study identified factors associated with states' adopting a mandate for regular staff testing for COVID-19 in NHs. Potential correlates included state government ideology and capacity, NH supply and demand, prevailing economic conditions, existing state policies, and NH characteristics. Findings indicate that percent for profit NHs is most strongly associated with adoption of a state staff testing mandate. Governing capacity (average legislative salary), percent population at risk for COVID-19, and existing public policy (percent Medicaid spending devoted to long-term services and supports (LTSS) were also associated with the probability of adoption. Based on these results, states with more proprietary facilities and greater capacities for government action, investment in Medicaid LTSS, and at-risk populations were more likely to mandate regular staff testing in NHs.